God's grace inscribed on the human heart: essays in honour of James R. Harrison - Bolt, Peter G.; Kim, Sehyun (SCD Press, 2022)
A collection of essays in honor of James R. Harrison, with contributions from Peter Arzt-Grabner, Richard S. Ascough, Paul Barnett, Stephen C. Barton, Bradley J. Bitner, Darrell L. Bock, Peter G. Bolt, Cilliers Breytenbach, Alan H. Cadwallader, Constantine R. Campbell, Doru Costache, John A. Davies, Kathy Ehrensperger, Joseph D. Fantin, Louise A. Gosbell, Edwin A. Judge, Rosalinde Kearsley, John S. Kloppenborg, Peter Lampe, Stephen Llewelyn and William Robinson, Harry O. Maier, Peter Oakes, Julien M. Ogereau, Neil Ormerod, Mark Reasoner, E. Randolph Richards, Guy MacLean Rogers, Benjamin Schliesser, Isaac T. Soon, Mark Stephens, Michael Trainor, Paul Trebilco, Samuel Vollenweider, and L. L. Welborn
Includes bibliographical references
Keywords: Harrison, James R -- 1952-